Thorough QTc Evaluation and the Safety of Supratherapeutic Doses of Odanacatib in Healthy Subjects. Issue 7 (7th June 2019) - McCrea, Jacqueline; Mostoller, Kate; Mahon, Chantal; Liu, Chengcheng; Liu, Fang; Zajic, Stefan; Panebianco, Deborah; Chakravarthy, Manu; Brandquist, Christine; Gutierrez, Maria; Stoch, S. Aubrey
Abstract: Assessing risk for QTc interval prolongation in a thorough QTc study is a standard recommendation when evaluating new chemical entities. As part of the clinical development program for odanacatib, an oral selective inhibitor of cathepsin K previously in development for the treatment of osteoporosis, 2 clinical studies in healthy subjects assessed pharmacokinetics and overall safety (including potential for delayed ventricular repolarization) of a supratherapeutic dose. In study 1, subjects received a supratherapeutic dose regimen of odanacatib (300 mg on day 1, then daily multiple doses of 25 mg to day 21) or placebo. In study 2 (days 1–4), subjects received the odanacatib supratherapeutic dose regimen or moxifloxacin (positive control, single 400‐mg dose on day 4; matching placebo for odanacatib/moxifloxacin) or placebo. All doses were administered with a high‐fat meal. In study 1 (N = 12), the supratherapeutic dosing regimen achieved exposure ∼3.5‐fold of the proposed therapeutic dose (50 mg once weekly) and was sufficiently well tolerated to permit assessment in the thorough QTc study (study 2). In study 2 (N = 116), the primary objective was placebo‐corrected change from baseline in QTcF interval (Fridericia's correction), assessed by replicate electrocardiograms (12‐lead Holter recordings; days –1 through 7). Supratherapeutic odanacatib dosing was not associated with increased risk of prolonged QT interval, unlike moxifloxacin (confirming assay sensitivity). Pooled safety data across both studies suggested that the safety profile of odanacatib at high exposures was similar to placebo, with a small clustering of oral cavity adverse events. Odanacatib was not associated with increased risk of prolonged QT interval.